Exchanging and managing in-vitro elite germplasm to combat cassava brown streak disease (CBSD) and cassava mosaic disease (CMD) in Eastern and Southern Africa - Tumwegamire, Silver; Kanju, E.; Legg, James P.; Shirima, R.; Kombo, S.; Mkamilo, G.S.; Mtunda, K.; Sichalwe, K.; Kulembeka, H.P.; Ndyetabura, I.; Saleh, H.; Kawuki, R.S.; et al. (Springer, 2018)
Cassava varieties resistant to cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) are needed for the food and income security of the rural poor in eastern and southern Africa (ESA). The International Institute of Tropical Agriculture led five national cassava breeding programs (Malawi, Mozambique, Kenya, Tanzania and Uganda) in virus-cleaning and exchanging elite cassava germplasm resistant to both diseases. This paper documents the experiences and lessons learned from the process. Thirty-one clones (25 elite, two standard and four national) were submitted by the five breeding programs to the Natural Resources Institute and Kenya Plant Health Inspectorate Services for virus cleaning and indexing. Subsequently, ca 75 in-vitro virus-indexed plantlets per clone were sent to Genetic Technologies International Limited (GTIL), a private tissue culture (TC) lab in Kenya, and micro-propagated to produce ≥1500 plantlets. After fulfilling all the formal procedures of germplasm exchange between countries ≥300 plantlets per clone were sent to each partner country. National check clones susceptible to CMD/CBSD were sent only to their countries of origin. In each country, the in-vitro plantlets were acclimatized under screen house conditions and transferred to clean isolated sites for field multiplication. All the clones were cleaned of the viruses, except Tomo. The cleaning process was slow for F19-NL, NASE1, and Kibandameno and TC micro-propagation at GTIL was less efficient for Pwani, Tajirika, NASE1, and Okhumelela than for the other clones. Difficulties in cleaning recalcitrant clones affected the timeline for establishing the multi-site evaluation trials in target countries. The initiative is the one of the kind to successfully clean and exchange elite germplasm as a joint action to combat CBSD in ESA. Adequate preparation in terms of infrastructure and personnel are critical to successfully receiving and adapting the indexed in-vitro plants as new germplasm.